The Effect of Price Discount and Electronic Word of Mouth on Purchase Intention with Brand Image as a Mediator (A Case Study of Generation Z Coffee Consumers in Surabaya) - Anam, Syaiful; Daniel, Joseph Robert (Journal Research of Social Science, Economics, and Management, 2026)
The rapid growth of social media and digital platforms has transformed consumer behavior, particularly among Generation Z, who increasingly rely on online information and promotional offers when making purchasing decisions. In Indonesia, TikTok has emerged as a key marketing channel, with local brands like Kopi Kenangan leveraging discounts and electronic word of mouth (e-WOM) to engage young consumers. However, the interplay between price incentives, digital recommendations, and brand perception remains underexplored in the context of coffee consumption. The purpose of this research is to determine the effect of price discounts and e-WOM on buying interest through the mediating role of brand image. The data source for this study is primary data. The sampling technique used was purposive sampling, with a total of 400 Generation Z respondents in the city of Surabaya. Data collection was conducted through the distribution of questionnaires. This study employs the SEM-PLS analysis method using the SmartPLS version 4.0 data processing tool. The results indicate that price discounts and e-WOM have a significant effect on brand image. In addition, price discounts, e-WOM, and brand image have also been proven to significantly influence buying interest. The findings further reveal that brand image mediates the influence of price discounts and e-WOM on buying interest.